Economic valuation of wetland resources: evidence from resource-dependent households in northern Nigeria - Yacob, Mohd Rusli; Adamu, Abdullahi; Kabir, Ibrahim; Ibrahim, Muhammad Sanusi (International Organization of Scientific Research, 2023)
In an effort to evaluate the economic benefit of conservation, the respondents’ willingness to pay for conservation was evaluated. Dichotomous-choice contingent valuation method (DC-CVM was employed on 393 households in communities surrounding the wetland. Binary Logistic regression was used in estimating the CVM model. The results of the analyses showed that75.8% of the the respondents were willing to pay for the conservation of HadejiNguru wetland. The result from the CVM model revealed that gender, age, education level, gross monthly income, bids amount, membership of environmental organisation, pro-environmental attitude and knowledge about the importance of the wetland were significant determinants of the willingness to pay. The result also revealed that the mean willingness to pay amount was estimated at N 2,324.08 ≈ USD 6.46 per household. The overall total use benefit of conservation of the wetland was estimated at N 3,486,120,000 (USD 9,683,666.67). The outcome of this study presents a compelling business case for wetland conservation in the Hadejia-Nguru wetlands, as it provides vital information that would guide policy makers on social return on investment in conservation. Therefore, for long term sustainability of the wetlands being an important resource pool that supports millions of local population, institutional and management structures that would guarantee its sustenance and promote wise use need to be in place. Also, there is the need for policy option that would be acceptable to all stake holders especially the local people, where they will be adequately represented as important stakeholders in decision making process.